Utility of Serum Allergy Test In Patients With Chronic Urticaria - Bhattarai, Sabina; Pradhan, K; Sharma, S; Pant, AD (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Chronic urticaria (CU) is a common skin disorder affecting 15– 20% of the people in the general population. It is a frequent disease which presents with wheals, angiooedema or both and lasts for over six weeks or more. OBJECTIVES: To determine the etiology of IgE specific allergens in the causative of CU in the Nepalese population. MATERIALS & METHODS: A prospective cross sectional study was carried out between November 2014- October 2016 on all patients diagnosed as having CU. Blood samples were taken from all patients and asemiquantitative determination of IgE antibodies against a panel of individual allergens was done and data analyzed and interpreted in terms of numbers and percentages. RESULTS: Three hundred and fourteen patients were included in the study with 56% (175) being female and 44% (139) being male. The age of the patients ranged from 5years to 84 years with a mean of 37.33± 14.39 years. The duration of the disease also ranged from 0.15 to 20 years in which 116(36.9%) patients presented with disease of less than 6 months duration while 163(51.9%) patients had the disease for more than 6 months. Two hundred and seventy nine patients (88.9%) showed a positive test to the allergens amongst which most were allergic to plants which included weeds and grass. CONCLUSION: In patients with CU whenever possible it is advisable to send the patient for serum allergy test to determine the causative agent, the avoidance of which can help in the management of urticaria in troublesome patients. Journal of Universal College of Medical Sciences (2017) Vol.05 No.01 Issue 15, Page: 33-36